2019
DOI: 10.1021/acs.macromol.9b01195
|View full text |Cite
|
Sign up to set email alerts
|

Processing Pathways Decide Polymer Properties at the Molecular Level

Abstract: Conditions of rapid processing often drive polymers to adopt nonequilibrium molecular conformations, which, in turn, can give rise to structural, dynamical, and mechanical properties that are significantly different from those in thermodynamic equilibrium. However, despite the possibility to control the desired nonequilibrium properties of polymers, a rigorous microscopic understanding of the processing–property relations is currently lacking. In an attempt to stimulate progress along this topical direction, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
127
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(130 citation statements)
references
References 94 publications
2
127
1
Order By: Relevance
“…In conclusion, we have shown that simple material processing-the deposition of thin polymer melts via spin coating-allows reaching a nonequilibrium regime where dynamics speeds up with increasing roughness, not otherwise achievable via equilibrium pathways [20]. Our results are in disagreement with the predictions of simulations that aim to treat rough substrates, largely because prior such work has failed to capture roughness on an experimentally relevant scale.…”
contrasting
confidence: 53%
See 1 more Smart Citation
“…In conclusion, we have shown that simple material processing-the deposition of thin polymer melts via spin coating-allows reaching a nonequilibrium regime where dynamics speeds up with increasing roughness, not otherwise achievable via equilibrium pathways [20]. Our results are in disagreement with the predictions of simulations that aim to treat rough substrates, largely because prior such work has failed to capture roughness on an experimentally relevant scale.…”
contrasting
confidence: 53%
“…We demonstrate that this unexpected trend is due to a reduction in density in proximity of rougher substrates. The results are discussed in terms of very stable nonequilibrium conformations [20], and within the framework of recent models considering a perturbation in interfacial free volume content (molecular packing) at the origin of confinement effects on glassy dynamics [21,22].…”
mentioning
confidence: 99%
“…Samples were first heated at 743 K for 10 s. Such a preliminary procedure aims to erase the thermo-mechanical history induced by spin-coating. This marks an important difference with previous adsorption experiments, where heating was limited to T g +60 K, which is not enough to erase conformational peculiarities induced by spin-coating 44 . After this preliminary procedure, samples were cooled down at 4000 K s −1 and immediately reheated with 10 4 K s −1 up to 743 K to collect a reference scan.…”
Section: Methodsmentioning
confidence: 64%
“…This is an important aspect as polymers often fail to equilibrate on the time scale of a typical processing experiment, and exhibits nonequilibrium behavior. 80 To do that, we have performed annealing experiments carried out for up to 35 h at 231 K, i.e., in the temperature region at which deviation from the bulk dynamics is expected. The samples were rapidly cooled from room temperature to selected annealing temperature and measured as a function of time employing the BDS technique.…”
Section: Resultsmentioning
confidence: 99%